Evaluation of the Exposure to Benzene and SpmA using the Urine of Workers in the Shoe Home Industry in Surabaya - Rizaldy Fathur Rachman; Iin Zulaiha Tuasikal; Abdul Rohim Tualeka; Trias Mahmudiono; Suwardi Suwardi (Universitas Airlangga, 2022)
Introduction: Benzene is one of the pollutants in the shoe home industry that can cause cancer among the workers. The present research aimed to analyze the relationship between exposure to benzene and spmA (s-phenylmercapturic Acid) in the urine of shoe-making home industry workers in Surabaya. Methods: This was an observational study using an analytical research method where the total number of respondents in the sample was 10. The concentration of benzene was measured using Gas Chromatography-FID (Flame Ionization Detector). The data collection technique was descriptive analysis for each variable from among the worker’s characteristics. The analysis of the relationship between the level of spmA in their urine and the worker’s characteristics was performed using regression tests while the analysis of the relationship between the level of benzene in the air and the levels of workers’ spmA was performed using the Spearman correlation test. Results: The benzene I levels in the work environment were found to be between 0.06 ppm - 53.8 ppm. The average spmA was 6.68 μg/g creatinine. The p value of the relationship between the variable levels of benzene and the levels of spmA was 0.879 with a Spearman correlation coefficient of 0.056. Conclusion: The mean concentration of benzene in the air at the 6 point uptake was over the threshold. Based on the results of the spmA examination, the mean value of spmA was below the threshold value. The test results on the level of benzene in the air and the spmA indicate a very weak relationship.